Arthroscopic Versus Open Treatment for Acute Septic Arthritis of the Knee in Children. Issue 5 (May 2018) - Johns, Brenton; Loewenthal, Mark; Ho, Eric; Dewar, David
Abstract : Background: Acute septic arthritis of the knee in children may be treated by arthroscopic or open methods; however, pediatric data comparing these methods is limited regarding both short- and long-term outcomes. This study aimed to compare outcomes after arthroscopic versus open surgery for acute pediatric septic knee arthritis. Methods: Pediatric patients with acute knee septic arthritis treated at our institution from 1996 to 2016 were retrospectively assessed. The clinical presentations, operations, microorganisms, laboratory results, knee radiologic findings and antibiotics administered were compared. Patients' long-term outcomes were assessed at mean 6.9 (range 1.1–20.3) years. Results: Twenty-four patients met the inclusion criteria. Eleven patients received arthroscopic irrigation and 13 had open irrigation. Five patients in the open group (38.5%) required a second irrigation compared with none in the arthroscopic group [95% confidence interval (CI): 12%–65%; P = 0.041]. Time to range the knee occurred earlier in the arthroscopic group (5.0 days; arthroscopic vs. 10.6 days; open, difference 5.6 days: 95% CI: 0.84–10.3, P = 0.023), as well as weight-bearing (2.7 days; arthroscopic vs. 10.3 days; open, difference 7.6 days: 95% CI: 2.3–12.9, P = 0.008). Eighty-three percent of patients attended follow-up. No infections recurred. No significant differences were found in Knee injury and Osteoarthritis Outcome Scores for children, Lysholm scores, range-of-motion, leg length, gait and radiologic findings. Conclusions: For acute pediatric septic knee arthritis, arthroscopic irrigation is associated with less repeat surgical irrigations and allows earlier knee ranging and weight-bearing compared with open irrigation. At long-term follow-up, no significant difference was found between groups.